Owning the body in the mirror: The effect of visual perspective and mirror view on the full-body illusion - Preston, Catherine (Sci Rep, 2015)
Mirrors allow us to view our own body from a third-person (observer) perspective. However, how viewing ourselves through a mirror affects central body representations compared with true third-person perspective is not fully understood. Across a series of experiments, multisensory full-body illusions were used to modulate feelings of ownership over a mannequin body that was viewed from a third-person perspective through a mirror, from a third-person perspective without a mirror, and from a first-person perspective. In contrast to non-mirror third-person perspective, synchronously touching the participant’s actual body and the mannequin body viewed in the mirror elicited strong feelings of ownership over the mannequin and increased physiological responses to the mannequin being threatened compared to the equivalent asynchronous (non-ownership) control condition. Subjective reports of ownership viewing the mannequin through a mirror were also statistically equivalent to those following the first-person perspective illusion. These findings suggest that mirrors have a special role for viewing the self. The results also support the importance of egocentric reference frames for body ownership and suggest that mirror reflections of one’s own body are related to peripersonal space, which enables updating of central body representations.